A Result regarding the Seismic Dislocations in Microstretch Thermoelastic Bodies. (2nd March 2015) - Marin, M.; Florea, O.; Mahmoud, S. R.
Abstract : The aim of our study is to derive a relation of De Hoop-Knopoff type for displacement fields within context of thermoelastic microstretch bodies. Then, as a consequence, an explicit expression of the body loadings equivalent to a seismic dislocation is obtained. The results are extensions of those from the classical theory of elastic bodies.